PELATIHAN APLIKASI QUIZIZZ DAN CANVA SEBAGAI MEDIA PEMBELAJARAN BAGI GURU-GURU DI SSVS JUNIOR HIGH SCHOOL HAT YAI, SONGKHLA, THAILAND - Murinto; Agus Akhtawan; Dedi Wijayanti (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract Since Covid-19 hit in 2020, all teaching and learning activities have been carried out online. These online teaching and learning activities have encouraged many IT companies to develop supporting applications either for face-to-face online or for making study materials or materials. The International Community Service Team (PkM) is a service program for UAD lecturers so they can take part at the international level. This is a program of the UAD Research and Community Service Institute (LPPM). One of the PkM teams that held PkM in Thailand was a team consisting of 2 lecturers from the Faculty of Industrial Technology (Dr. Murinto, S.Sc., M.Kom) and 1 lecturer from the Faculty of Teaching and Science (Dedi WIjayanti, S.Pd. , M. Hum). The training was held on 02 and 03 August 2023, 2 lecturers (representatives of the PkM Team) from the Faculty of Industrial Technology had the opportunity to hold International Community Service activities for teachers at Songserm Sasana Vittaya School (SSVS), Hat Yai, Thailand. Songserm Sasana Vittaya School (SSVS), in Hat Yai, Songkhla, Thailand., is a junior high school in Thailand that has an MoU with Ahmad Dahlan University. One form of cooperation is having a work program to develop and improve and create the competitiveness of the community, especially teachers so as to create superior teachers accompanied by the use of technology. The problem that occurs with SSVS teachers is that not all teachers have the ability to utilize digital literacy technologies, namely Canva and Quizizz. This service to the international community is also assisted by 4 UAD alumni who are currently teaching at Songserm Sasana Vittaya School (SSVS), Hat Yai, Thailand. Prior to the training, the coordination and preparation of the training was carried out. The training was attended by 15 participants, who were teachers from various subjects at SSVS Junior High School. This training was conducted in an offline form at the Songserm Sasana Vittaya School (SSVS) computer laboratory. Besides the training being carried out offline in its implementation, after the training, mentoring was also carried out by providing information and examples of poster sources that could be accessed. So that participants can repeat the training material at their respective homes. Monitoring and evaluation is how teachers implement what has been taught during training. Implementation in schools directly. Monitoring will be done online by the PkM Team. This training had a considerable impact, namely 90% of teachers found it easier to use the applications being taught and were satisfied. Abstrak Sejak Covid-19 menerpa pada tahun 2020, semua kegiatan belajar-mengajar dilakukan secara online atau daring. Kegiatan belajar-mengajar secara daring tersebut mendorong banyak perusahaan IT mengembangkan aplikasi-aplikasi penunjang baik untuk tatap muka online atau membuat bahan atau materi belajar. Tim Pengabdian kepada Masyarakat (PkM) Internasional merupakan program pengabdian dosen-dosen UAD agar bisa berkiprah di level internasioanl. Ini merupakan program dari Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UAD). Salah satu Tim PkM yang mengadakan PkM di Thailand adalah Tim yang terdiri dari 2 dosen Fakultas Teknologi Industri (Dr. Murinto, S.Si., M.Kom) dan 1 dosen dari Fakultas Keguruan dan Ilmu Pengetahuan ( Dedi WIjayanti, S.Pd., M.Hum). Pelatihan diadakan pada tanggal 02 dan 03 Agustus 2023, 2 dosen (merupakan perwakilan Tim PkM) dari Fakultas Teknologi Industri berkesempatan mengadakan kegiatan Pengabdian kepada Masyarakat Internasional bagi guru-guru di Songserm Sasana Vittaya School (SSVS), Hat Yai, Thailand. Songserm Sasana Vittaya School (SSVS), di Hat Yai, Songkhla, Thailand., merupakan suatu sekolah menengah pertama di Thailand yang mempunyai MoU dengan Universitas Ahmad Dahlan. Salah satu bentuk kerja samanya adalah mempunyai program kerja mengembangkan dan meningkatkan serta menciptakan daya saing civitas terutama guru sehingga tercipta pengajar yang unggul disertai pemanfaatan teknologi. Permasalahan yang terjadi pada guru-guru SSVS adalah belum semua guru memiliki kemampuan memanfaatkan teknologi literasi digital yaitu Canva dan Quizizz. Pengabdian kepada Masyarakat Internasional ini juga dibantu oleh 4 alumni UAD yang sedang menjadi guru di Songserm Sasana Vittaya School (SSVS), Hat Yai, Thailand. Sebelum pelatihan dilakukan terlebih dahulu koordinasi dan persiapan pelatihan. Pelatihan diikuti oleh 15 peserta, merupakan guru-guru dari berbagai mata Pelajaran yang ada di SSVS Junior High School. Pelatihan ini dilakukan dalam bentuk offline bertempat di ruang laboratorium komputer Songserm Sasana Vittaya School (SSVS). Disamping pelatihan dilakukan secara offline dalam pelaksanaannya, setelah pelatihan juga dilakukan pendampingan dengan memberikan informasi dan contoh-contoh sumber poster yang dapat diakses. Sehingga peserta dapat mengulang kembali materi pelatihan di rumah masing masing. Monitoring dan evaluasi adalah bagaimana guru-guru mengimplementasikan apa yang sudah diajarkan saat pelatihan. Implementasi di sekolah secara langsung. Pemantauan akan secara daring oleh Tim PkM. Pelatihan ini memberikan dampak cukup besar yaitu 90% para guru merasa lebih mudah menggunakan aplikasi yang diajarkan dan merasa puas.